Update of photobiomodulation in oral mucositis: a systematic review - Labrosse Géraldine; Graillon Nicolas; Maladiere Eric; Lan Romain; Campana Fabrice (EDP Sciences, 2022)
Introduction: Oral mucositis (OM) is a common side effect of radiotherapy (RT) or radio-chemotherapy (RT/CT) for head and neck cancers. It causes lesions leading to impairment of the quality of life, dysphagia, pain, and in up to 20% of cases, a dosimetry concession, decreasing local tumor control, thereby impacting the survival rate. Positive results of photobiomodulation (PBM) to treat it have been reported in the literature. PBM has multiple parameters (type of laser, emission mode, number of sessions to be performed, wavelength, power, energy, fluence, exposure time, number of points) making it difficult to implement in clinical practice. Materials and methods: A literature search strategy was applied in Medline by selecting articles published between 2010 and 2020 to answer the following research question: "In patients treated with RT or RT/CT, what is the place of PBM in the management of OM?", in accordance with PICO (patient, intervention, comparison and outcomes) criteria. The inclusion criteria were all original articles (clinical cases and clinical studies) which answered the research question. Meta-analyses, systematic reviews of the literature and journals, animal or in vitro studies, studies published in a language other than French or English, and full-text articles not accessible via inter-university credits were excluded. Results: Seventeen articles were included, representing 1576 patients. The PBM was intraoral in 16 papers and combined intra- and extra-oral emission in 1 paper. InGaAlP diode laser and HeNe laser significantly reduced OM compared with placebo in 62.5% and 75% of the studies, respectively. Pain reduction was poorly or not documented and when it was, it did not correlate with the reduction of analgesics. Temporary or permanent interruption of radiotherapy was also poorly documented. Discussion: The MASCC/ISOO (2019) report is an important step forward to establish a reproducible protocol for PBM, which as our results show, is heterogeneous in use. Our results showed that the studies started PBM on the first day of RT, using a wavelength of 660 nm for diode laser and 632.8 nm for HeNe laser. However, there is no scientific evidence vis-à-vis the values for power, energy, fluence, exposure time, or number of points. Although PBM appears to be effective in reducing OM scores, its effectiveness on improving patient quality of life, pain, painkiller consumption, compliance with treatment and the occurrence of complications remains to be defined. The relationship between PBM and survival rate was not an objective of this work. We found that of the 17 articles, 15 stated that they did not illuminate the tumor site during PBM sessions. Conclusion: The main objective of this work was to determine the place of PBM in the treatment of OM. Overall, the results on OM scores were favorable in almost ¾ of the studies. Despite its efficacy, the questions of the adjustment of the parameters of PBM, the harmonization on OM scale and its safety on carcinologic recurrence remain to be studied. In view of the lack of comparability of studies and the lack of reported data, studies that harmonize endpoints and follow-up criteria are needed to establish a standard protocol.